2022
DOI: 10.1136/bjsports-2021-104994
|View full text |Cite
|
Sign up to set email alerts
|

Train at home, but not alone: a randomised controlled multicentre trial assessing the effects of live-streamed tele-exercise during COVID-19-related lockdowns

Abstract: ObjectivePublic life restrictions associated with the COVID-19 pandemic caused reductions in physical activity (PA) and decreases in mental and somatic health. Considering the interplay between these factors, we investigated the effects of digital home exercise (DHE) during government-enforced lockdowns.MethodsA multicentre randomised controlled trial was performed allocating healthy individuals from nine countries (N=763; 523 female) to a DHE or an inactive control group. During the 4-week main intervention, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 50 publications
0
19
0
1
Order By: Relevance
“…As a consequence, it seems of paramount importance to identify ways to maintain or even enhance PA during restrictions. One effective method to achieve this while social distancing is through tele-exercise, which has recently been shown to be efficacious in this context [ 46 ]. In addition, digital technologies (i.e., telehealth) could be used to promote and counsel on PA without in-person contact.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, it seems of paramount importance to identify ways to maintain or even enhance PA during restrictions. One effective method to achieve this while social distancing is through tele-exercise, which has recently been shown to be efficacious in this context [ 46 ]. In addition, digital technologies (i.e., telehealth) could be used to promote and counsel on PA without in-person contact.…”
Section: Discussionmentioning
confidence: 99%
“…All 25 articles included in this review were RCTs published from 2020 to 2022 in seventeen countries, including the United Kingdom ( n = 3; Gilbody et al, 2021; Liang et al, 2022; Wadhen & Cartwright, 2021), China ( n = 2; Rong et al, 2021; Wong et al, 2021), Israel ( n = 2; Gidron et al, 2021; Shapira et al, 2021), Switzerland ( n = 1; Brog et al, 2022), Australia ( n = 1; Bryant et al, 2022), Italy ( n = 1; Carbone et al, 2021), Spain ( n = 2; Catuara‐Solarz et al, 2021; Puertas‐Gonzalez et al, 2022), Germany ( n = 3; Heckendorf et al, 2022; Preuss et al, 2021; Wilke et al, 2022), the United States of America ( n = 1; Kahlon et al, 2021), Malaysia ( n = 1; Kim, 2020), New Zealand ( n = 1; Loveys et al, 2021), India ( n = 2; Muniswamy et al, 2021; Pal et al, 2022), Sweden ( n = 1; Pellas et al, 2021), Serbia ( n = 1; Vukčević Marković et al, 2020), Korea ( n = 1; Yi & Yim, 2021), Canada ( n = 1; Beauchet et al, 2022), and Turkey ( n = 1; Tekin & Cetisli‐Korkmaz, 2022). The characteristics of the 25 studies are reported in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The effects decreased over time during the four-week livestreaming period, however, and the opposite trend was observed when the livestreaming was replaced with prerecorded exercise videos. 37 However, the rate of regular LTPA was not shown, and measuring MVPA and VPA in the previous week is not the same as regular LTPA. Therefore, the improvement in MVPA and VPA over four weeks that was shown in that study does not necessarily mean that the participants had formed a habit of regular exercise.…”
Section: Discussionmentioning
confidence: 99%
“…First, besides combining aerobic training, resistance exercises, and dynamic balance training, 45 we also developed a multicomponent exercise program that could be used during the COVID-19 pandemic. 37 Secondly, through the use of self-management techniques (such as recording their exercise behavior), the participants were reminded to exercise, had an enhanced motivation to exercise, and could more easily form a habit of exercising. 45 …”
Section: Discussionmentioning
confidence: 99%